Register Komunitas Jual-Beli Ponsel Cerdas di Grup Facebook: Studi Kasus Kota Yogyakarta: Register in smartphone buy-and-sell community on Facebook group: case study of Yogyakarta city - Ariefandi, Febryan (Journal of Literature and Education, 2024)
Other than social media, Facebook also has a special feature called Forum Jual Beli (FJB), which functions as a medium for buying, selling, or promoting products among fellow users. During transactions, it is not uncommon for Facebook users to use a special lexicon that can only be understood by its members. This study aims to describe the process of register lexicon formation and the function of its use in the smartphone buy and sell community on Facebook named Group Jual Beli Handphone Yogyakarta. The type of research is descriptive-qualitative with a sociolinguistics approach. The theories used to analyze the data include Kridalaksana's (1989) morphological process and Halliday's (1973) language function. Based on the results of the research, the process of word formation found includes affixation, composition, acronyms, clipping, abbreviations, and zero derivation. When viewed from its function, the register of the smartphone buy-and-sell community on FJB group fulfills instrumental, regulatory, representational, and heuristic functions.